Standards of nasal provocation tests - Samoliński, Bolesław; Rapiejko, Piotr; Krzych-Fałta, Edyta; Gotlib, Tomasz; Emeryk, Andrzej; Buczyłko, Krzysztof; Chełmińska, Marta; Chełmiński, Konrad; Niedoszytko, Marek; Świerczyńska-Kępa, Monika; Kupczyk, Maciej; Sybilsk, Adam; et al. (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
The nasal allergen provocation test (NAPT) plays an important role in diagnosis of allergy. It is based on the natural reaction of the nasal mucosa after application of tested substances on their surface. Nasal challenges are divided into specific (allergenic) and non-specific. Typical clinical symptoms depend on the immunological reaction: sneezing, itching, rhinorrhea and nasal blockage. Eosinophilic mucosal infiltration is observed in the late phase reaction. Typically the result of nasal challenge should be assessed by the physician and patient. The immunological reaction, especially the level of particular allergenic mediators, could also be investigated. Some objective methods for final assessment of the results are recommended. There is some information about non-specific nasal provocation with aspirin and occupational diseases in the paper.